Comparative metabolic profiling of wild Cordyceps species and their substituents by liquid chromatography-tandem mass spectrometry - Guo, Shan; Lin, Manting; Xie, Di; Zhang, Wenqing; Zhang, Mi; Zhou, Li; Li, Sheng; Hu, Hankun (Frontiers in Pharmacology, 2022)
Cordyceps is a genus of ascomycete fungi and used widely in fungal drugs. However, in-depth studies of the metabolites of wild Cordyceps species and their substituents are lacking. In this study, a liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based metabolomics analysis was carried out to comprehensively profile the metabolites in wild Chinese Cordyceps species (Ophiocordyceps sinensis (Berk.) G.H. Sung, J.M. Sung, Hywel-Jones & Spatafora 2007) from Naqu (NCs) and Yushu (YCs) and their substituents including artificially cultivated Cordyceps species (CCs) and mycelia. A total of 901 metabolites were identified in these samples, including lipids, amino acids, nucleosides, carbohydrates, organic acids, coenzymes, vitamins, alkaloids and their derivatives. Univariate and multivariate statistical analyses revealed remarkable differences and significantly different metabolites among them. Seventy amino acid-relevant metabolites were analyzed quantitatively in four samples for the first time. The four samples contained abundant L-glutamic acid and oxidized glutathione as well as multiple unique amino acid-relevant metabolites (e.g., 3-chloro-L-tyrosine, 6-aminocaproic acid, L-theanine, anserine, γ-glutamyl-cysteine). Collectively, our study provides rich metabolic information of wild Cordyceps species and their substituents, which could facilitate their quality control and optimal utilization.